PARADIGM OF ELECTRONIC MEASUREMENTS: FROM ERROR TO UNCERTAINT - Tarasenko, Y.; Prokopovych-Tkachenko, D.; Savchenko, I.; Voskoboynik, V. (Systems and Technologies, 2021)
The article is devoted to the conceptual issues of organizing and conducting radio-electronic measurements. The results of the study indicate that the adequacy and reliability of the compliance of electronic measurements within the framework of the use of the uncertainty principle should be identified both with the nature of a posteriori measurement results and with the development of a solution for the errors attributed to them in possible intervals in the form of some deviations, which reflects the presence of the fact of measurement uncertainty. The analysis shows that the traceability of measurement results to the International System of Units (SI) is carried out by calibration, provided by a competent laboratory, using certified standard samples with certified values of a competent manufacturer with specified metrological traceability to SI and by direct implementation of SI units. direct or indirect comparisons with national or international standards. The paradigm of reliability of conformity of measurements in the course of their realization according to modern requirements of the last ISO recommendations in Ukraine is provided by legislative requirements on creation of laboratories on calibration. At the same time, these services with a wide variety of measurements are able to cover a limited part related to determining the reliability of measurement measures in accordance with the international measurement system. The results of the study can actually state that the adequacy and reliability of electronic measurements in the application of the uncertainty principle should be identified with the issuance of a posteriori measurement results and with the development of decisions on the errors attributed to them and possible intervals of their errors in the form of some deviations reflects the fact of measurement uncertainty.